1998
DOI: 10.1021/bc970180a
|View full text |Cite
|
Sign up to set email alerts
|

Extending Insulin Action in Vivo by Conjugation to Carboxymethyl Dextran

Abstract: The biochemical and pharmacological properties of bioactive peptides and proteins can be altered by conjugation with polymers. This report describes site-specific attachment of insulin to activated carboxyl groups of carboxymethyl dextran (CMD, MW=51000) through the GlyA1 insulin amino group. On average, three or four insulin molecules were grafted to a CMD linear chain. Coupled insulin molecules were properly folded, and the bioactivity of conjugated insulin in the blood glucose depression assay was 9.6 IU/mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Other examples include dextran conjugates of asparaginase, carboxypeptidase G 2 , and hemoglobin, respectively, as well as CMD‐insulin conjugates …”
Section: Carbohydrate Polymersmentioning
confidence: 99%
“…Other examples include dextran conjugates of asparaginase, carboxypeptidase G 2 , and hemoglobin, respectively, as well as CMD‐insulin conjugates …”
Section: Carbohydrate Polymersmentioning
confidence: 99%
“…For example, native insulin was typically released when the insulin releasing mechanism involves matrix swelling, matrix disassembly or degradation. In the case of glucose binding competition induced insulin release, the working insulin released was typically an insulin modified with polymers, such as dextran-insulin conjugate, [93] or small molecules, such as succinyl amidophenyl glucopyranoside [32]. It is particularly important to examine the bioactivity of the modified insulin.…”
Section: Evaluation Of Grir Systemmentioning
confidence: 99%
“…It is particularly important to examine the bioactivity of the modified insulin. Reports show that conjugating dextran to insulin loses 60–90% of native insulin bioactivity [93,94]. Thus, a significantly higher molar dose of conjugated insulin has to be delivered than unmodified native insulin in achieving comparable glucose suppressive effect.…”
Section: Evaluation Of Grir Systemmentioning
confidence: 99%
“…Investigators have demonstrated a direct correlation between the M W of the coupled dextran and the increase in the conjugate's half-life [52]. Other examples of protein-dextran conjugates include: uricase [54], superoxide dismutase [55], insulin [56] and hemoglobin [57,58]. Readers can refer to Mehva's review for an exhaustive overview of all dextran conjugates, including those with low M W s [43].…”
Section: Dextranmentioning
confidence: 99%